Empowerment and social justice values, theory and action - Prilleltensky, Isaac, 1959-; Microtraining and Multicultural Development (Firm); Microtraining Associates ([North Amherst, Mass.] : Distributed by Microtraining Associates, Inc., 2007)
Looks at the values of a caring collective community; provides specifics for social justice practice
2006 Winter Roundtable Teachers College, Columbia University
Presenter :Isaac Prilleltensky
Keywords: Community psychology; Community power; Social psychology